PENGARUH FEAR OF MISSING OUT TERHADAP IMPULSE BUYING PRODUK FASHION SHOPEE DI KOTA PALEMBANG - Vinatan, Tristama; Lina, Lina; Tyra, Maria Josephine (LPPM Universitas Multi Data Palembang, 2025)
This study aims to determine the effect of fear of missing out (FOMO) on impulse buying of fashion products that occurs through the Shopee marketplace, especially in Palembang. The data used in this research is primary data. The population in this study are people in the city of Palembang who use the Shopee application. The sampling technique used was a purposive sampling method and obtained 50 samples. Hypothesis testing is done by multiple regression analysis. The results of this study indicate that partially, fears and worries have a positive and significant effect on impulse buying, while anxieties have a positive but not significant effect on impulse buying. Simultaneously, fears, worries, and anxieties have a positive and significant effect on impulse buying.